Peningkatan Kompetensi Guru dalam Menyusun Penelitian Tindakan Kelas melalui Pendidikan dan Pelatihan di MAN 1 Sleman - Soir (Jurnal Pendidikan Madrasah, 2022)
Classroom Action Research (PTK) is one of the factors that affect teacher competence. Improvement of learning in the classroom can be done through classroom action research because it places teachers as researchers, as agents of change whose work patterns are creative and innovative. This study aims to improve competence in compiling PTK through education and training. This research is an action research carried out in two cycles including planning, action, observation, and reflection activities. Data collection techniques use observation, interviews and evaluation. The results of education and training to compile PTK show that teachers actively participate in compiling PTK. PTK training activities have an impact on increasing significant knowledge about understanding PTK data processing and analysis. The training process improves teacher understanding of ptk, fosters motivation in compiling PTK and implementing PTK, and improves madrasah performance through increasing teacher professionalism. The results of this research can be used as input for teachers in other madrasahs as an effort to improve teacher competence through Classroom Action Research.